EFEK MODERASI TIPE INDUSTRI DALAM HUBUNGAN ESG DISCLOSURE TERHADAP FIRM VALUE: STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Febria Agatha Br Sembiring (Komunitas Manajemen Kompetitif, 2026)
The awareness of adopting Environmental, Social, and Governance (ESG) principles has become a crucial issue in achieving corporate sustainability and attracting investor interest in the capital market. This study aims to examine the effect of ESG disclosure on firm value and analyze the role of industry type as a moderating variable. The research objects include companies listed on the Indonesia Stock Exchange from 2020 to 2024 that met the purposive sampling criteria, resulting in a total of 250 observations. ESG disclosure, as the independent variable, is measured using ESG scores, while the dependent variable is firm value, measured through market valuation proxies. Data analysis was conducted using the panel data regression method with a Fixed Effect Robust model. The results of this study indicate that ESG disclosure does not have a significant effect on firm value. Furthermore, the industry type variable was found to be unable to moderate the relationship between ESG and firm value. This suggests that investors in Indonesia have not yet utilized ESG information as a primary fundamental factor in investment decision-making that impacts market valuation. These findings also demonstrate a homogeneity in disclosure across various industrial sectors, which tends to be performed as a form of compliance with financial authority regulations rather than a strategic effort to enhance firm value